2020
DOI: 10.18410/jebmh/2020/594
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oral Submucous Fibrosis in a Tertiary Care Hospital of Odisha - A Cross-Sectional Study

Abstract: BACKGROUND Oral Sub Mucous Fibrosis (OSMF) is the most common precancerous lesion prevalent in Asian subcontinent and India. It raises concern among oral healthcare professionals because among all potentially malignant oral lesions and conditions, this precancerous condition has highest rates of malignant transformation. The aim of our study is to evaluate the prevalence of OSMF in habitual areca nut chewers among the patients attending the out-patient Department of Dentistry of Veer Surendra Sai Medical Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
0
0
Order By: Relevance
“…In this study, out of 30 cases 20 were males (67%) and 10 (33%) were females which clearly showed a male predominance. Similar observations have been reported in other studies 21,22 . This is due to easy accessibility of areca nut based products, use of areca nut and related products by co-workers/closely associated people at work place or people in the immediate surroundings.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, out of 30 cases 20 were males (67%) and 10 (33%) were females which clearly showed a male predominance. Similar observations have been reported in other studies 21,22 . This is due to easy accessibility of areca nut based products, use of areca nut and related products by co-workers/closely associated people at work place or people in the immediate surroundings.…”
Section: Discussionsupporting
confidence: 93%
“…In this study we found a significant association of disease severity with mouth opening i.e., there was a decrease in the inter-incisal mouth opening of the patients from stage I of OSMF to stage II, stage III, and stage IV respectively. The mean mouth opening of patients with different stages of OSMF was by studies reporting the mean mouth opening of patients with advanced stages of OSMF to be less than 15mm 18,19 .…”
Section: Resultsmentioning
confidence: 99%